The future of NATO : enlargement, Russia, and European security - David, Charles Philippe; Lévesque, Jacques (Foreign policy, security, and strategic studies., 1999)
The Future of NATO looks at the conceptual and theoretical approaches that underlie the question of enlarging NATO's membership and the consequences of enlargement on international relations. It examines the policies of some of NATO's leading member states - including Canada, which has recently begun a two-year term on the security council - and deals with the issue of enlargement from the point of view of the East European candidates, focusing on Russia and its opposition to the current process. Contributors include Andràs Balogh (Loràn Eötvös University), Martin Bourgeois, Charles-Philippe David (UQAM), André P. Donneur (UQAM), David G. Haglund (Queen's), Philippe Hébert (Montréal), Stanislav J. Kirschbaum (Glendon College), Richard L. Kugler (RAND, National Defence University), David Law (Queen's), Paul Létourneau (Montréal), Jacques Lévesque (UQAM), Gale Mattox (U.S. Naval Academy), Marie-Claude Plantin (Lumière Lyon 2), Sergei Plekhanov (York), Jane M.O. Sharp (Kings College, London).